New Era of Credit Analysis - CM, Vidya (Ushus Journal of Business Management, 2018)
Credit analysis is the evaluation of the credit worthiness of a business or an organisation done through historic data like audited balance sheets, forecasts in the form of budgets and cash flow, ratings given by credit rating companies, analysis of ratios, capital marketisation, share prices and many more benchmarks. However, in today’s world, “Big Data” is what is being spoken about by all. Data is collected every second from various sources like social media sites, online and offline purchases and so on. The emerging era of credit analysis is based on consumer behaviour online; their likes and dislikes, preference for the products they purchase and so on. Everything is recorded through “Big Data” and is accessible to judge whether a person is worthy of credit or not. All these are studied through complicated mathematical computations to analyse sequences of information within an ocean of data. These credit scorings can be provided within no time and are equally cost-efficient. The study focusses on the effectiveness of big data for credit analysis.